The Efficacy and Safety of a Low-Dose Tranexamic Acid Bolus-Only Protocol Compared with the Moderate-Dose Protocol in Valvular Heart Surgery - Koster, Andreas; Hulde, Nikolai; Deutsch, Marcus-Andre; Gummert, Jan F.; von Dossow, Vera; Zittermann, Armin (The Thoracic and Cardiovascular Surgeon, 2023)
In 873 propensity score–matched pairs of patients undergoing valvular heart surgery, we compared a “moderate dose” of tranexamic acid (TXA) protocol (group 1; median TXA dose: 24 mg/kg body weight) with a 1.5-g “bolus-only” protocol (group 2; median TXA dose: 19 mg/kg body weight). The number of transfused patients was higher in group 2 than in group 1 (74.5 vs 66.0%, p < 0.001), as was the number of transfused red blood cell concentrates (p = 0.001). The risks of re-exploration and convulsive seizures were similar between groups (p > 0.50). Data indicate an impaired efficacy following the “bolus-only” protocol, without a significant safety improvement.
Keywords: cardiac; anesthesia; blood transfusion; heart valve surgery; neurology/neurologic